An integrated assessment modeling tool - Carmichael, J; Tansey, J; Robinson, J (2004)
The Georgia Basin Futures Project is an innovative regional scale integrated assessment (IA) exercise, which is being undertaken for the purpose of identifying futures that are desirable to the general publicin a region, and for the assessment of appropriate policy approaches to realizing these desired futures. Georgia Basin (GB)-QUEST is an interdisciplinary computer-modelling tool which was developed, based on an earlier prototype, as a central part of this project. This paper describes how GB-QUEST is organized, which IA principles are central to its design, the modelling techniques being employed and the experience of users of the model. The paper suggests that the particular modelling methods used, in combination with the innovative design approach, represents a viable template for future regional IAs. r 2004 Elsevier Ltd. All rights reserved.